Efek Paket “Tabahanmil” terhadap Pengetahuan, Sikap dan Ketrampilan Ibu Hamil dalam Mencegah Perdarahan - Eko Riyanti; Irna Nursanti; Natsir Hugroho (Journal of Telenursing (JOTING), 2019)
The purpose of this study was to determine the effect of the package of warning signs of bleeding pregnant women (tabahanmil) on the knowledge, attitudes and skills of pregnant women in preventing bleeding in Bayan District, Purworejo Regency. The type of quantitative research with Quasi experimental research design, pretest-posttest with control group design. The results of bivariate analysis found that the intervention group after being given a tabahanmil package significantly affected compared to the control group that was not given a tabahanmil package on knowledge, attitudes, and skills, each of which has a p value = 0,000 less than 0.05. Conclusion, there is a significant difference from the average value of knowledge, attitudes, and skills of pregnant women in preventing bleeding in the intervention group and the control group. Keywords: Pregnant Women, Skills, Preventing Bleeding, Knowledge, Attitudes